2017
DOI: 10.1111/1462-2920.13940
|View full text |Cite
|
Sign up to set email alerts
|

Phototrophic microbes form endolithic biofilms in ikaite tufa columns (SW Greenland)

Abstract: Marine tufa-columns, formed by the hydrated carbonate mineral ikaite, present a unique alkaline microbial habitat only found in Ikka Fjord (SW-Greenland). The outermost parts of the ikaite columns exhibit a multitude of physico-chemical gradients, and the porous ikaite is colonized by endolithic phototrophic biofilms serving as a substrate for grazing epifauna, where scraping by sea urchins affects overall column-topography. We present a detailed study of the optical microenvironment, spatial organization, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…BSL tufa mounds have shown to host diverse and active microbiota, which stratify from the tufa surface to its interior by following the water mixing gradient, therefore, providing wider ecological niches where the BSL microbiota thrive. These results add to the increasing evidence demonstrating the importance of groundwater effluents in active microbialites (Warden et al, 2019), the diversity of microbial communities inhabiting carbonate tufas (Russell et al, 2014; Trampe et al, 2017), and the key role of microbes in the formation of tufa mounds (Brasier et al, 2018; DeMott et al, 2020). In addition, we showed that microbial ureolysis in BSL tufa biofilms—demonstrated not simply by the presence of their genes, but also by in situ measurement of their activity—potentially increase tufa growth rates by maintaining a highly alkaline microenvironment in concert with EPS‐degrading metabolisms that release calcium.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…BSL tufa mounds have shown to host diverse and active microbiota, which stratify from the tufa surface to its interior by following the water mixing gradient, therefore, providing wider ecological niches where the BSL microbiota thrive. These results add to the increasing evidence demonstrating the importance of groundwater effluents in active microbialites (Warden et al, 2019), the diversity of microbial communities inhabiting carbonate tufas (Russell et al, 2014; Trampe et al, 2017), and the key role of microbes in the formation of tufa mounds (Brasier et al, 2018; DeMott et al, 2020). In addition, we showed that microbial ureolysis in BSL tufa biofilms—demonstrated not simply by the presence of their genes, but also by in situ measurement of their activity—potentially increase tufa growth rates by maintaining a highly alkaline microenvironment in concert with EPS‐degrading metabolisms that release calcium.…”
Section: Discussionsupporting
confidence: 64%
“…Green and brown biofilms are pervasive on the surface of subaqueous tufas, whereas conspicuous microbial mats were absent on subaerial portions (Figure 2; Video S1). Subaerial tufas, however, host microbes both in tufa crevasses and inside carbonate minerals themselves (Figure 2b), where they form endolithic communities (e.g., Guida et al, 2017; Trampe et al, 2017; Walker et al, 2005). Light and fluorescence microscopy shows abundant, likely photosynthetic, green filaments attached to mineral grains on surficial biofilms from subaqueous tufa samples, along with diatoms, nematodes, and small motile bacteria (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The clustering pattern could suggest that the microbial communities within each column exhibit some level of specialization based on their location from top to bottom within the column. This could be due to variations in environmental factors, such as availability of light, oxygen, and nutrients ( Trampe, 2016 ; Trampe et al, 2016 , 2017 ). The latter could be explained by our findings of anaerobic bacteria and archaea primarily in the middle and bottom sections of the columns.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, the ikaite columns contain a rich diversity of extremophilic prokaryotic organisms adapted to life at low temperature and high pH ( Stougaard et al, 2002 ; Schmidt et al, 2006a , b , 2007 ; Schmidt et al, 2012 ; Glaring et al, 2015 ). A few studies have previously identified eukaryotic organisms living in association with the ikaite columns ( Kristiansen and Kristiansen, 1999 ; Sørensen and Kristensen, 2000 ; Thorbjørn and Petersen, 2003 ; Trampe et al, 2017 ), and a single study used a sequencing-based approach to briefly look into the eukaryotic diversity inside the columns ( Stougaard et al, 2002 ). But aside from seven identified 18S rRNA gene sequences representing different phylotypes with low levels sequence similarities to (then) known 18S rRNA genes, the eukaryotic diversity inside the ikaite columns has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies used advanced microcopy to visualize the presence of mixed-species biofilms. In a study by Trampe et al ( 2017 ), they sampled underwater minerals (ikaite) from a fjord located in Greenland and found that algae (diatoms) and cyanobacteria co-existed on these minerals and were embedded in polymeric substances (Trampe et al, 2017 ). Biofilms in sediments are also frequently studied.…”
Section: Environmental Biofilmsmentioning
confidence: 99%